A history of Australian tort law 1901-1945 : England's obedient servant? / Mark Lunney. - Lunney, Mark (Law in context., 2018)
Little attention has been paid to the development of Australian private law throughout the first half of the twentieth century. Using the law of tort as an example, Mark Lunney argues that Australian contributions to common law development need to be viewed in the context of the British race patriotism that characterised the intellectual and cultural milieu of Australian legal practitioners. Using not only primary legal materials but also newspapers and other secondary sources, he traces Australian developments to what Australian lawyers viewed as British common law. The interaction between formal legal doctrine and the wider Australian contexts in which that doctrine applied provided considerable opportunities for nuanced innovation in both the legal rules themselves and in their application. This book will be of interest to both lawyers and historians keen to see how notions of Australian identity have contributed to the development of an Australian law.